(untitled) (Bulletin KNOB, 2007)
A floating cellar is a brickwork basin that can be moved up and down with the groundwater level. It is a relatively unknown phenomenon with a history in which all sorts of fascinating questions are intermingled. Besides dealing with the water, technical conditions in the field of making mortar, brickwork and pumping, the final fixing of the floating cellar basins and the problems of protection are ingredients for a closer look at the phenomenon. In the sixteenth and seventeenth centuries Amsterdam went through a few impressive growing pains resulting, among other things, in the ambition to utilise the available space in the merchants’ houses in the town as much as possible. The scarce land available was usually more expensive than raising or deepening the already existing buildings. A recurrent problem was that cellar floors kept bursting open because of the strong upward water pressure as a result of peaks in the height of the groundwater level due to tides and storm floods. It is not quite clear when the first real floating cellar was built in Amsterdam. It was probably around the middle of the seventeenth century. The earliest drawing of such a specimen known so far was published in 1674 by the well-known master builder Philips Vingboons. In 1701 the municipality prescribed a maximum depth for cellar floors of just above town level. It is likely that the wider application of floating cellars did not take place until after this regulation. Special characteristics of floating cellars are the bonds in shiner courses of bricks on their flat sides and the use of trass mortar so as to be able to make watertight brickwork. The Amsterdam floating cellars were fixed after 1871, when the town water level was stabilised by the construction of the Oranje sluices. Floating cellars were also found in surrounding Dutch towns and villages. Without exception these are situated in the lowest areas with a relatively high and unstabilised groundwater level. Most of them date from the nineteenth century. An older and still functioning specimen is to be found in Edam. Since a few years the phenomenon has been studied systematically by the Bureau Monumenten & Archeologie in Amsterdam.